Effects of Initial Porosity and Water Pressure on Seepage-Erosion Properties of Water Inrush in Completely Weathered Granite - Jinquan Liu; Weizhong Chen; Taogen Liu; Jianxin Yu; Jingliang Dong; Wen Nie (Geofluids)
In order to investigate the water inrush mechanism in completely weathered granite, a large-scale triaxial testing system is designed and manufactured, which can induce the mass transfer and monitor the flow properties. Using this system, the effects of water pressure and initial porosity on the mass transfer and flow properties were determined, and the relative critical conditions for water inrush were proposed. The results indicate that (1) the particle transfer could cause an increase in porosity, permeability, and water inflow, which is the essential reason for water inrush in completely weathered granite. (2) Due to the effect of particle transfer, the flow properties may change from a Darcy to a non-Darcy flow, which is a key signal for water inrush. (3) With the increase of water pressure, the mass transfer, permeability, and water inflow increased gradually, and a critical value (p=0.6 MPa) that caused the water inrush was obtained. Furthermore, with the decrease of initial porosity, the mass transfer and flow properties were suppressed rapidly, and a critical porosity (0.23) to anti-inrush was observed. The results obtained can provide an important reference for understanding the mechanism, forecasting the risk, and taking the effective control measures for water inrush.